Like Nobody's Business: An Insider's Guide to How US University Finances Really Work - Andrew C. Comrie (Open Book Publishers, 2021)
"How do university finances really work? From flagship public research universities to small, private liberal arts colleges, there are few aspects of these institutions associated with more confusion, myths or lack of understanding than how they fund themselves and function in the business of higher education. Using simple, approachable explanations supported by clear illustrations, this book takes the reader on an engaging and enlightening tour of how the money flows. How does the university really pay for itself? Why do tuition and fees rise so fast? Why do universities lose money on research? Do most donations go to athletics? Grounded in hard data, original analyses, and the practical experience of a seasoned administrator, this book provides refreshingly clear answers and comprehensive insights for anyone on or off campus who is interested in the business of the university: how it earns its money, how it spends it, and how it all works."–Publisher's website
Keywords: 370; university finances; tuition fees; research; donations; Hochschulfinanzierung; USA